A new species of Leptalpheus Williams, 1965 and new records of L. mexicanus Ríos & Carvacho, 1983 and L. hendrickxi Anker, 2011 (Crustacea: Decapoda: Alpheidae) from the Pacific coast of Mexico - Salgado-Barragán, José; Ayón-Parente, Manuel; Hendrickx, Michel E. (Zootaxa, 2014)
A new species of Leptalpheus is described from Estero Pérula, Jalisco, on the Pacific coast of Mexico. Leptalpheus corderoae sp. nov. is most similar to Leptalpheus azuero Anker, 2011 from Panama and Leptalpheus axianassae Dworschak & Coelho, 1999 from Brazil, differing from both of them by a combination of morphological characters, especially the presence of tubercles on the ventral surface of the major chela palm and pollex. The most common host of L. corderoae sp. nov. at the type locality is the callianassid ghost shrimp Lepidophthalmus bocourti (A. Milne Edwards, 1870). Additional specimens of Leptalpheus mexicanus Ríos & Carvacho, 1983, from Estero de Urías, Sinaloa, are reported and compared to the type material from Río Mulegé, as well as to Leptalpheus bicristatus Anker, 2011 from Panama. Finally, Leptalpheus hendrickxi Anker, 2011 is reported from Mexico for the first time, representing a significant northward range extension of the species. In Estero Pérula, L. hendrickxi lives in burrows of Lepidophthalmus bocourti, sometimes together with L. corderoae sp. nov.